Attendees for the 1962 Monte Toyon II Camp. - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the Monte Toyon II Camp, held August 18-25, 1962 in Santa Rosa, California. Small groups of attendees can be seen holding signs and banners that read: "St. Mark's!," "Santa Rosa," "Morris II Boo Boo (any friend of Zorro's is a friend of ours)."